An Investigation into Microstructures and Mechanical Properties of 1060 Pure Aluminum during Submerged Friction Stir Processing at a High Rotating Speed - Yuchen Peng; Qi Zhang; Lingyou Wen; Zonghua Xie; Biao Huang; Shanshan Hu; Hongqun Tang; Chunhua Wei (Metals, 2022)
In this work, 1060 pure aluminum was subjected to high rotating speed submerged friction stir processing (HRS-SFSP). The heat cycle curve of the processing area was measured by K-type thermocouple and temperature recorder. The microstructure, grain size, texture, and tensile fracture of the processing area were analyzed by electron backscattered diffraction and scanning electron microscopy. The results show that the HRS-SFSP caused severe plastic deformation of 1060 aluminum and produced fine recrystallized grains. The minimum average grain size was 0.686 μm at the 2-pass. In addition, the dislocation density in the stirred region was greatly reduced and the high angle grain boundaries (HAGBs) were dominant. The texture strength of pure aluminum increased with the increase in processing passes. The maximum hardness of 66.3 HV and ultimate tensile strength of 95.2 MPa were obtained at 1-pass, which were 86% and 33.9% higher than those of the base material, respectively. The hardness and strength of the stirring zone (SZ) decreased with the increase in the number of processing passes. Therefore, HRS-SFSP pure aluminum can obtain high strength and hardness while maintaining good plasticity.